Juridification of ESG in European Union Law: An Analysis of the CSRD and CSDDD from the Perspective of Public Economic Law and Environmental Protection Law - Justyna PRZEDANSKA (Communications of International Proceedings, 2025)
This article analyses the juridification of Environmental, Social and Governance (ESG) frameworks in European Union law through an examination of two key regulatory instruments: the Corporate Sustainability Reporting Directive (CSRD, Directive (EU) 2022/2464) and the Corporate Sustainability Due Diligence Directive (CSDDD, Directive (EU) 2024/1760). The motivation for the study lies in the growing role of ESG in EU economic regulation and the observable shift from voluntary, managerial standards towards binding public-law obligations addressed to undertakings operating on the EU market. While existing literature extensively examines ESG from managerial, financial and organisational perspectives, it has paid comparatively limited attention to the public-law dimension of ESG as a regulatory category. In particular, there is a lack of integrated legal analysis treating the CSRD and the CSDDD as elements of a single, coherent regulatory regime rather than as isolated instruments. This article addresses that gap by analysing the combined regulatory logic and effects of these Directives from the perspectives of public economic law and environmental protection law. The research is based on doctrinal legal analysis combined with systemic and functional interpretation of EU law. It examines the normative structure, regulatory assumptions and legal consequences of the CSRD and the CSDDD, situating them within the broader architecture of EU sustainability regulation. The article demonstrates that, taken together, the CSRD and the CSDDD juridify ESG by coupling compelled transparency with substantive due diligence obligations across the chain of activities. This regulatory model shifts the protection of environmental and human rights interests upstream to corporate planning and risk management, while simultaneously generating regulatory tensions related to proportionality, formalisation and the risk of procedural compliance without substantive change.
Keywords: CSRD; CSDDD; corporate sustainability due diligence; sustainability reporting